A Flexible Approach to Imaging in ABSL-3 Laboratories. (June 2015) - Dennis, Mike J.; Parks, Simon; Bell, Gordon; Taylor, Irene; Lakeman, Jody; Sharpe, Sally A.
In-life imaging of animals challenged experimentally with infectious agents greatly enhances the quality of data gained from a pathogenesis or efficacy study. This additional information also presents an opportunity to address ethical issues by refining the studies and reducing the number of animals used. Both magnetic resonance (MR) and computed tomography (CT) imaging modalities are used extensively in human medicine to diagnose disease and to monitor the efficacy of treatments. To make animal-based studies as relevant as possible to the clinical situation, such technologies must be applied wherever possible. Imaging animals infected with disease-causing agents presents a number of challenges for programs that assure health and safety as well as the well-being of the animals during the scanning process.